Terapia Analítico-Comportamental: análise de processos e resultados em estudos de sujeito único (N=1) - Moron, Sara Gonzalez (Universidade Federal de São Carlos, 2022)
Mental illness is a problematic increasing in the mental health scope around the globe. Nowadays, psychotherapy is one of the treatments recommended for this complex issue, been used different theoretical references. Between the therapeutic approaches in Brazil there is the Analytical Behavioral Therapy (ABT), based in the Radical Behaviorism with the intervention focused on the analysis of contingencies active in the analyzed individual’s or group’s context. Recent studies about the process and outcome in ABT have been emphasizing the need of more research with the mean of description of the process and outcome, aiming to amplify evidences of efficacy and efficiency. Between many discussions, it is more urgent the need to delimitate an intervention’s procedure, in group and individually, in procedures with few sessions, i. e., a ABT brief psychotherapy model. The present study aimed to describe a brief psychological support program based in ABT, planed to be developed in up to 12 individual sessions of 50 minutes, weekly. The process developed in this procedure was detailed in its different phases. The main goals of a group of sessions were outlined, the main procedures implemented described, the instruments used outlined, trying to emphasize especially the goal of the therapist in this process. Also, examples of products were inserted, from the intervention with three participants referred from the wait list of the service, offered by a public university in the state of São Paulo. For the insertion of the cases in the present study, the design was submitted and approved by the Ethics Committee for Human Research. General and initial considerations allow the discussion about some difficulties with the model, remote and face-to-face application possibilities and indicating possible paths for future research.
Analytical Behavioral Therapy: process and outcome analysis in a single-case study (N=1)
Keywords: Terapia Analítico-Comportamental (TAC); Psicoterapia breve; Pesquisa de processos; Analytical Behavioral Therapy (ABT); Brief psychotherapy; Process research; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA